A PANI–Cellulose acetate composite as a selective and sensitive chemomechanical actuator for acetone detection. (2nd January 2016) - Mojtabavi, Mehrnaz; Jodhani, Gagan; Rao, Ramya; Zhang, Jing; Gouma, Perena
Abstract: This study addresses the role of PANI–CA composites in the detection of acetone vapors with high sensitivity and selectivity in the presence of alcohols. The PANI–CA composites were fabricated by the solution-casting method and were cut to 4 cm × 3 mm rectangular strips of about 20-μm thickness. The composite strips behave as gas sensors/chemoactuators and respond to gaseous species by converting their relative concentration to a corresponding mechanical motion (bending). The bending-recovery responses of PANI/CA sensor was examined thoroughly by exposing it to varying headspace concentrations of acetone and alcohols, and by removing the analyte once the sensor reached its maximum bending angle. Sensitivity was determined by comparing the bending response of the composite strips to different headspace concentrations of acetone. Selectivity was determined through analysis of the angle change in 50/50 ml solutions of four different (potentially interfering) chemicals. The results indicate that the sensor highly discriminates between acetone and alcohols making it a potential wearable acetone skin sensor for indirect measurement of glucose in the blood for diabetics. Graphical abstract: